THE CONCEPT OF HUMAN BEHAVIOR IN A REVIEW OF ISLAMIC ECONOMIC PHILOSOPHY - M. Rikwan E.S. Manik; M. Yasir Nasution; Sugianto (JESKaPe: Jurnal Ekonomi Syariah, Akuntansi dan Perbankan, 2022)
Human behavior is formed from the way he thinks. There are two dominant ideologies of human thinking today, the ideology of capitalism which is the dominant ideology throughout the world and is the benchmark for the actions of the majority of society. The separation of religion from life is the principle that gave rise to this ideology. Meanwhile, the ideology of socialism, even though it has experienced an era of destruction, is still being fought for by its fanatical followers. This ideology emerged from the concept of materialism. Concern and worry, perhaps two words that should be said relate to the behavioral problems that plague humanity today towards human behavior. For this reason, this study will try to unravel how the concept of human behavior in a review of Islamic economic philosophy uses descriptive qualitative research using secondary data. The results of this study describe that humans have a tendency to behave well or behave badly. There is a negative element in the soul in the form of lust (al-ghadhab and al-syahwat), so that humans have good behavior they must use reason to grasp al-hikmat, both al-hikmat al-'ilmiyyat al-nazhariyyah (theoretical wisdom) which is captured by reason theoretical and also al-hikmat al-khuluqiyyat (practical wisdom). These two balances (al-hikmat) become the control of al-ghadhab and al-lust.